THE PERSPECTIVE OF KYAI PARAK BAMBU RUNCING ISLAMIC SCHOOL STUDENTS TO BUDDHISM AS TOLERANCE STUDYING SOURCE: PANDANGAN SANTRI PONDOK PESANTREN KYAI PARAK BAMBU RUNCING TERHADAP AGAMA BUDDHA SEBAGAI SUMBER BELAJAR TOLERANSI - Junarsih, Junarsih; Widiyono, Widiyono; Suranto, Suranto (Jurnal Pencerahan, 2020)
Around 4 years ago Dwipaloka Monastery in Parakan subdistrict was located in front of Kyai Parak Bambu Runcing Moslem School and their harmonious relationship was very good. That made me so interested in making a deep research about the perspective of students there about Buddhism. This Moslem school is one of the salaf Muslim schools which means the students just only study Islamic knowledge diligently while living side by side with Buddhist people. Therefore, this research is aimed to know about Muslim students' tolerance to Buddhist people and serves a tolerance learning source. This research used a qualitative method with case studies. Techniques and instruments for the data collection were done by interview, observation, and documentation. The results of this research include five things as the tolerance learning source, i.e: (a) the teachers' activities for emphasizing tolerance to the Muslim students; (b) the meaning of tolerance for teachers and Muslim students; (c) Muslim students' knowledge about Buddhism concerning on religious leaders in Buddhism, the name of the holy book in Buddhism, Vesakh, and the Buddha's teaching; (d) the range of Muslim students’' tolerance; and (e) Muslim students' tolerance base on theory, textual, and practice.